2017
DOI: 10.1177/0886260517741215
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Psychological Abuse: The Role of Perpetrator Gender, Victim’s Response, and Sexism

Abstract: It is commonly assumed that male abuse is more damaging than female abuse, just as it previously has been assumed that physical abuse is more harmful than psychological abuse. We sought to examine gender assumptions given that they may cause people to overlook the harm that men experience with a psychologically abusive partner. The current experiment compared perceptions of male and female perpetrators of psychological abuse, and examined whether gendered perceptions were affected by sexist beliefs or particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…Although psychology often emphasizes differences in construal, we suspect both subjective and objective differences in men-as-partners and women-as-partners are responsible for instigating breakups. Men are, in fact, much more likely than women to engage in harmful behaviors following breakups, including various addictions and mental and/or physical partner abuse (Capezza, D’Intino, Flynn, & Arriaga, 2017; Reid et al, 2008). Thus, our findings may also reflect gender differences happening in romantic relationships, with women actually being more supportive than men vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Although psychology often emphasizes differences in construal, we suspect both subjective and objective differences in men-as-partners and women-as-partners are responsible for instigating breakups. Men are, in fact, much more likely than women to engage in harmful behaviors following breakups, including various addictions and mental and/or physical partner abuse (Capezza, D’Intino, Flynn, & Arriaga, 2017; Reid et al, 2008). Thus, our findings may also reflect gender differences happening in romantic relationships, with women actually being more supportive than men vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions of physical abuse may be so firmly established that they effect perceptions of emotional abuse and result in harsher judgements of males (Capezza, D'Intino, Flynn, Arriaga, 2017). Capezza et al (2017) found that participants rated male perpetrators of emotional abuse more harshly than they did female perpetrators. However, ratings were unaffected by the gender of the participants themselves.…”
Section: Review Of Findingsmentioning
confidence: 98%
“…Psychological IPV often comes first and is an important risk factor for physical IPV [ 4 , 6 ]. It has been reported that perceived abuse severity and the perpetrator’s responsibility differ according to the type of abuse (non-physical or physical) [ 7 ], as well as the gender of the victim and the perpetrator aggressor [ 8 ]. Thus, physical abuse is considered to be more severe than non-physical abuse, and these associations hold whether it is male towards female, or female on male abuse [ 9 ].…”
Section: Introductionmentioning
confidence: 99%